Is there an athlete`s artery? A comparison of brachial and femoral artery structure and function in male strength, power and endurance athletes - Naylor, L. H.; Spence, A. L.; Donker, S. C. M.; Thijssen, D. H. J.; Green, D. J. (Journal of Science and Medicine in Sport, 2021)
Objectives: Exercise places physiological demands upon the cardiovascular system, subsequently leading to adaptations in structure and function. Different exercise modalities (endurance, strength and power) lead to distinct hemodynamic demands and, possibly, different patterns of adaptation. Our aim was to assess and compare brachial and femoral artery function and structure in elite level athletes engaged in endurance, strength and power sports. Design: cross sectional comparison. Methods: 30 male elite athletes (runners n = 10, powerlifters n = 11, weightlifters n = 9) and 23 healthy controls were recruited. Brachial and femoral arterial diameters were assessed using ultrasound. Arterial function (brachial and femoral arteries) was determined using the flow mediated dilation (FMD) technique and body composition using body mass index (BMI) and body surface area (BSA). Results: Weightlifters had significantly larger brachial arterial diameters compared to controls (4.39 ± 0.34 vs 3.86 ± 0.42 mm, p < 0.01). As weightlifter and power athletes had significantly higher body mass, BMI and BSA, we adjusted diameter for BSA. BSA-correction ameliorated differences in brachial artery resting diameters between athletes and controls. However, BSA-corrected femoral artery diameter was significantly larger in runners compared to controls (3.51 ± 0.28 vs 3.25 ± 0.34 mm, p < 0.05). There were no differences in brachial FMD between groups. Femoral artery FMD was significantly higher in runners and weightlifters compared to controls (p < 0.05 for both groups). Conclusions: Heterogeneous, limb-specific structural and functional vascular adaptation is evident in athletes, which may be influenced by exercise modality. Further, vascular remodelling relates to differences in body shape, specifically body composition, which should be accounted for when comparing athletes.